RESEPSI IMAJINER AL-QUR - Alim, Adinda Putri; Wendry, Novizal; Hanif, Muhammad (Jurnal Studi Agama dan Masyarakat, 2023)
The visual representation of the Qur'an in animated movies found in the movie Riko The Series Season I serves as a framework for this research. Children's digital content is filled with this representation, which highlights the advancements in modern science. The purpose of this essay is to investigate how the Qur'an is interpreted in the movie, which highlights the importance of Quranic science in each of its segments. This study employs a qualitative methodology, interpreting data according to two classifications of al-Qur'anic reception; exegetical and functional. According to this study, the actors in the Qur'an illustrate how the text is interpreted in popular culture. In one instance, an actor named Riko poses a question, to which another actor named Qiio responds with knowledge from both science and the Qur'an. The animated video's topics center on the creation of things, human ingenuity, indications of Allah's magnificence, interpersonal relationships, and the injunction to worship. According to the author, the animated movie shifts how the Qur'an is interpreted from the real world to the realm of imagination.